Ten new species of Polyosma (Escalloniaceae) from Borneo - Saw, Leng Guan (Phytotaxa, 2020)
Twenty species of Polyosma are currently recorded for Borneo, ten are new and they are described here: P. cyanoides, P. dewildei, P. fulva, P. glabrescens, P. grandiflora, P. matangensis, P. melanophylla, P. murudensis, P. parvifolia and P. pseudobracteosa. Provisional conservation assessments are made for all the newly described species. One species is assessed Endangered (EN), four Vulnerable (VU), one Near Threatened (NT), one Least Concern (LC) and three Data Deficient (DD).